WHY CHOOSING SOCIAL RESPONSIBILITY ACTIONS OVER PLANNED INVESTMENTS IN POTENTIAL WORLD WAR III - Angela-Alexandra VALACHE-DARINGA (Oradea Journal of Business and Economics)
Given nowadays economic issues and challenges on large scale, social responsibility actions became much more appealing over the planned investments at the European Union level for the defense and potential conflicts in case of the third war. This article undertakes a qualitative theoretical approach and aims to answer the question through Chabot interaction of what would be the savings in choosing planned investments in social responsibility action to feed the entire population over investment for the defense of the population in case of war. One basic human right is the access to adequate food, right that if far of being accessible worldwide. As food security is a question of environmental and social justice, the value of this paper findings is addressed to international organizations, policy makers, stakeholders and citizens. We can become more aware about the fact that we all are sharing a collective responsibility in increasing economic growth and social well-being. We can contribute today, in 2025, to boost food security in order to achieve economic access to sufficient safe and nutrition food and that the actual investment for the future would priorities both security and sustainability actions.